Refractive error after phacoemulsification combined with intraocular lens implantation in primary angle-closure glaucoma: a multifactorial analysis of biometric parameters and surgical strategies - Liu, Yong; Dang, Kuanrong; Gong, Di; Deng, Simin; Deng, Yin; Guo, Junhong; Shen, Xiaoli; Wang, Jiantao (Frontiers in Cell and Developmental Biology, 2025)
PurposeThis study aims to explore the factors influencing refractive error following Phacoemulsification combined with intraocular lens implantation (PE + IOL) in patients with primary angle-closure glaucoma (PACG), providing a theoretical basis for preoperative consultation and IOL power selection in clinical practice.MethodsA retrospective analysis was conducted on 404 PACG patients from Shenzhen Eye Hospital between 2019 and 2024. Preoperative ocular biometric parameters and combined surgical approaches were evaluated using Spearman correlation, multinomial logistic regression, and receiver operating characteristic (ROC) curve analysis.ResultsAxial length (AL), lens thickness (LT), and white-to-white distance (WTW) were key predictive factors for prediction error and postoperative refractive outcomes. AL > 22.56 mm (AUC = 0.692) and LT > 5.055 mm (AUC = 0.633) increased the risk of myopic shift (MS), while AL < 22.25 mm (AUC = 0.604) and WTW <11.55 mm (OR = 2.209, P = 0.001) were associated with hyperopic shift (HS). The axial length/corneal radius (AL/CR) ratio >2.986 further indicated a higher risk of MS (AUC = 0.639) postoperatively. Among patients who underwent PE + IOL combined with capsular tension ring, the proportion of HS was significantly higher (Z value = +2.95).ConclusionThe unique anatomical characteristics of PACG patients are key contributors to postoperative refractive instability. Preoperative assessment for PE + IOL surgery should comprehensively evaluate AL, LT, WTW, and AL/CR ratio. When combined with other surgical approaches to control intraocular pressure, IOL power should be adjusted according to these thresholds to ensure postoperative refractive stability.